Identification of Energy Costs in The Gowongan Water Supply System of Perumda Air Minum Tirta Moedal, Semarang, Indonesia - Afriza Cahya Putri; Ali Masduqi; Suryanto Suryanto (Jurnal IPTEK, 2025)
Energy use in water supply systems has drawn increasing attention, especially in areas relying on pumps. This study evaluates the E4 pumps system at the Gowongan Water Supply System (SPAM) by Perumda Air Minum Tirta Moedal Semarang City, conducted in April 2025. Real-time measurements were taken using an ultrasonic flowmeter and a digital power meter. The analysis covered pump efficiency, Specific Energy Consumption (SEC), and electricity usage during peak (WBP) and off-peak (LWBP) hours, based on Ministry of Energy Regulation No. 7/2024. The results showed a pump efficiency of 60.3% and an SEC value of 0.221 kWh/m³. Over 83% of electricity was consumed during off-peak hours, indicating the effectiveness of the Variable Speed Drive (VSD) implementation. The audit also recommends optimizing pump operation schedules and exploring alternative energy sources as strategies to improve operational efficiency.